Rational Design of Advanced Photosensitizers Based on Orthogonal BODIPY Dimers to Finely Modulate Singlet Oxygen Generation. Issue 20 (21st March 2017) - Epelde‐Elezcano, Nerea; Palao, Eduardo; Manzano, Hegoi; Prieto‐Castañeda, Alejandro; Agarrabeitia, Antonia R.; Tabero, Andrea; Villanueva, Angeles; de la Moya, Santiago; López‐Arbeloa, Íñigo; Martínez‐Martínez, Virginia; Ortiz, María J.
Abstract: The synthesis, photophysical characterization, and modeling of a new library of halogen‐free photosensitizers (PS) based on orthogonal boron dipyrromethene (BODIPY) dimers are reported. Herein we establish key structural factors in order to enhance singlet oxygen generation by judiciously choosing the substitution patterns according to key electronic effects and synthetic accessibility factors. The photosensitization mechanism of orthogonal BODIPY dimers is demonstrated to be strongly related to their intrinsic intramolecular charge transfer (ICT) character through the spin‐orbit charge‐transfer intersystem crossing (SOCT‐ISC) mechanism. Thus, singlet oxygen generation can be effectively modulated through the solvent polarity and the presence of electron‐donating or withdrawing groups in one of the BODIPY units. The photodynamic therapy (PDT) activity is demonstrated by in vitro experiments, showing that selected photosensitizers are efficiently internalized into HeLa cells, exhibiting low dark toxicity and high phototoxicity, even at low PS concentration (0.05–5×10 −6  m ). Abstract : Toxic singlets : A new library of halogen‐free photosensitizers based on orthogonal boron dipyrromethene (BODIPY) dimers with different substitution patterns are reported as valuable platform molecules for advanced theragnosis agents, which are produced through low‐cost and straightforward synthetic routes.